2014
DOI: 10.1073/pnas.1319176111
|View full text |Cite
|
Sign up to set email alerts
|

CRTC1/MAML2 gain-of-function interactions with MYC create a gene signature predictive of cancers with CREB–MYC involvement

Abstract: Chimeric oncoproteins created by chromosomal translocations are among the most common genetic mutations associated with tumorigenesis. Malignant mucoepidermoid salivary gland tumors, as well as a growing number of solid epithelial-derived tumors, can arise from a recurrent t (11, 19)(q21;p13.1) translocation that generates an unusual chimeric cAMP response element binding protein (CREB)-regulated transcriptional coactivator 1 (CRTC1)/mastermindlike 2 (MAML2) (C1/M2) oncoprotein comprised of two transcriptional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 87 publications
0
17
0
Order By: Relevance
“…In biphenotypic sinonasal sarcoma, PAX3-MAML3 fusion genes had the same MAML3 breakpoint as in PCC/PGL and were not associated with increased expression of NOTCH target genes (Wang et al, 2014). On the other hand, the CRTC1-MAML2 fusion gene in mucoepidermoid carcinomas did affect NOTCH signaling (Enlund et al., 2004) and also had a gain-of-function interaction with Myc (Amelio et al, 2014), consistent with MYC overexpression in MAML3 fusion-positive PCC/PGLs. Future work may illuminate whether mastermind fusions in other tumor types lead to Wnt signaling pathway upregulation.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In biphenotypic sinonasal sarcoma, PAX3-MAML3 fusion genes had the same MAML3 breakpoint as in PCC/PGL and were not associated with increased expression of NOTCH target genes (Wang et al, 2014). On the other hand, the CRTC1-MAML2 fusion gene in mucoepidermoid carcinomas did affect NOTCH signaling (Enlund et al., 2004) and also had a gain-of-function interaction with Myc (Amelio et al, 2014), consistent with MYC overexpression in MAML3 fusion-positive PCC/PGLs. Future work may illuminate whether mastermind fusions in other tumor types lead to Wnt signaling pathway upregulation.…”
Section: Discussionmentioning
confidence: 85%
“…Fusion genes involving mastermind family members have been reported in other tumor types (Amelio et al, 2014; Enlund et al, 2004; Wang et al, 2014). In biphenotypic sinonasal sarcoma, PAX3-MAML3 fusion genes had the same MAML3 breakpoint as in PCC/PGL and were not associated with increased expression of NOTCH target genes (Wang et al, 2014).…”
Section: Discussionmentioning
confidence: 97%
“…It has been shown that ectopic expression of Mect1-Maml2 may be tumorigenic in rat epithelial cells, and inhibition of the fusion protein using RNA interference can suppress growth in fusion-positive MEC cell lines(40). A recent report suggests that the fusion protein may also interact with Myc and activate Myc transcription targets, including genes involved in cell growth, metabolism, survival, and tumorigenesis(41). These findings, along with lack of significant driver oncogene mutations in MEC, strongly suggest that MECT1-MAML2 translocation may be the main oncogenic driver in this tumor type.…”
Section: Discussionmentioning
confidence: 99%
“…Characterization of novel driver mutations and biomarkers could lead to treatment stratification paradigms and targeted therapy options to improve patient survival. As CRTC1 and CRTC3 are involved with cell cycle, and MAML2 is involved with cell differentiation, further analysis of mutations in cell cycle and cell differentiation pathways by next generation sequencing techniques may highlight new, and novel driver mutations in MECs [1922] . Previous studies have identified some genetic differences between low-grade MECs, and higher grade MECS, including copy number variations in SMAD4 , CDKN2A , DCC , and LYN , all cancer-associated genes [23] .…”
Section: Discussionmentioning
confidence: 99%